Dihydrolevoglucosenone (Cyrene™) as a bio-renewable solvent for Cu(0)wire-mediated reversible deactivation radical polymerization (RDRP) without external deoxygenation. Issue 17 (21st August 2020) - Marathianos, Arkadios; Liarou, Evelina; Hancox, Ellis; Grace, James L.; Lester, Daniel W.; Haddleton, David M.
Abstract : Biorenewable dihydrolevoglucosenone (Cyrene™) is used as an effective dipolar aprotic solvent for Cu(0) wire-mediated RDRP of various monomers without external deoxygenation being applied. Abstract : Biorenewable dihydrolevoglucosenone (Cyrene™) is used as an effective dipolar aprotic solvent for Cu(0) wire-mediated RDRP of various monomers without external deoxygenation being applied. The solvent is used to give products with a broad range of molar masses ( M n ∼ 700–28 000), in situ chain extension and as low as 7.8 × 10 −4 eq. of [Cu(ii )Br2 ] relative to initiator.